Use of performance standards in behavioral health carve-out contracts among Fortune 500 firms - Merrick, E L; Garnick, D W; Horgan, C M; Goldin, D; Hodgkin, D; Sciegaj, M (The American journal of managed care, 1999)
To determine the prevalence and nature of performance standards in specialty managed behavioral healthcare contracts among Fortune 500 companies. This was a cross-sectional survey of all companies listed on the Fortune 500 during 1994, 1995, or both. From April 1997 to May 1998 we conducted a mailed survey with phone follow-up. Of the 68% of firms that responded, over one third reported carve-out contracts. The survey focused on whether companies had behavioral health carve-out contracts with specialty vendors and characteristics of these contracts, including the use of performance standards. More than three quarters of the Fortune 500 companies reporting specialty behavioral healthcare contracts used at least one performance standard. Most common were administrative standards (70.2%) and customer service standards (69.4%). About half of the companies used quality standards, whereas only a third used provider-related standards. Most (58.8%) companies using performance standards also specified financial consequences. Larger Fortune 500 firms were significantly more likely to use performance standards. Risk contracts and contracts that included all covered employees were also more likely to include some categories of standards. Administrative and customer service standards may be most common because companies find it easier to specify those standards, especially compared with clinical quality measures. To the extent that employers want to obtain the most value from their behavioral healthcare purchasing, we expect that more will begin to adopt quality standards in their contracts, especially as performance measures become more refined. Reliance on accreditation, however, is an alternative approach for employers.